Genetic susceptibility of intervertebral disc degeneration among young Finnish adults - Kelempisioti Anthi; Eskola Pasi J; Okuloff Annaleena; Karjalainen Ulla; Takatalo Jani; Daavittila Iita; Niinimäki Jaakko; Sequeiros Roberto B; Tervonen Osmo; Solovieva Svetlana; Kao Patrick YP; Song You-Qiang; et al. (BMC, 2011)
Abstract Background Disc degeneration (DD) is a common condition that progresses with aging. Although the events leading to DD are not well understood, a significant genetic influence has been found. This study was undertaken to assess the association between relevant candidate gene polymorphisms and moderate DD in a well-defined and characterized cohort of young adults. Focusing on young age can be valuable in determining genetic predisposition to DD. Methods We investigated the associations of existing candidate genes for DD among 538 young adults with a mean age of 19 belonging to the 1986 Northern Finland Birth Cohort. Nineteen single nucleotide polymorphisms (SNP) in 16 genes were genotyped. We evaluated lumbar DD using the modified Pfirrmann classification and a 1.5-T magnetic resonance scanner for imaging. Results Of the 538 individuals studied, 46% had no degeneration, while 54% had DD and 51% of these had moderate DD. The risk of DD was significantly higher in subjects with an allele G of IL6 SNPs rs1800795 (OR 1.45, 95% CI 1.07-1.96) and rs1800797 (OR 1.37, 95% CI 1.02-1.85) in the additive inheritance model. The role of IL6 was further supported by the haplotype analysis, which resulted in an association between the GGG haplotype (SNPs rs1800797, rs1800796 and rs1800795) and DD with an OR of 1.51 (95% CI 1.11-2.04). In addition, we observed an association between DD and two other polymorphisms, SKT rs16924573 (OR 0.27 95% CI 0.07-0.96) and CILP rs2073711 in women (OR 2.04, 95% CI 1.07-3.89). Conclusion Our results indicate that IL6, SKT and CILP are involved in the etiology of DD among young adults.